The three musketeers. Part II, Milady [videorecording (DVD)] - Delaporte, Matthieu; La Patellière, Alexandre de, 1971-; Civil, François, 1989-; Cassel, Vincent, 1966-; Duris, Romain, 1974-; Marmaï, Pio; Green, Eva, 1980-; Bolduc, Nicolas, 1973-; Roussel, Guillaume, 1980-; Dumas, Alexandre, 1802-1870 (Samuel Goldwyn Films, 2024)
D'Artagnan is forced to join forces with Milady to save Constance, who was kidnapped before his eyes. But as war is declared and Athos, Porthos and Aramis have already joined the front, a secret from the past shatters old alliances.